1988
DOI: 10.1038/icb.1988.32
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological relationships between Vibrio fluvialis and Vibrio cholerae enterotoxins

Abstract: Summary A total of 26 strains of I 'ibriojiuvialis was included in this study, which were isolated from patients with diarrhoea and other sources. The GM i enzyme linked immunosorbent assays performed with the culture filtrates of I', fluvialis yielded negative results, indicating that their receptor site is different from that of the known labile toxin. The cholera antitoxin failed to neutralize the skin permeability factor activities of all the I ./7HV;(2//5 culture filtrates and none of the concentrated cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…In the animal models, V. fluvialis and the cholera toxin (CT) produced by V. cholerae O1 strains confirmed skin permeability factor (SPF). However, the antibodies against CT did not neutralize the SPF of V. fluvialis (Rodrigues et al, 1993; Ahsan et al, 1988). …”
Section: Virulence Factorsmentioning
confidence: 95%
“…In the animal models, V. fluvialis and the cholera toxin (CT) produced by V. cholerae O1 strains confirmed skin permeability factor (SPF). However, the antibodies against CT did not neutralize the SPF of V. fluvialis (Rodrigues et al, 1993; Ahsan et al, 1988). …”
Section: Virulence Factorsmentioning
confidence: 95%
“…[41][42][43][44] It has been reported that the enterotoxin it possesses differs from the cholera toxin of the Vibrio cholerae species both in the recipient and in the mode of action and antigenicity. 45 An isolated case of otitis caused by the species Vibrio fluvialis associated with the species Vibrio alginolyticus has been recently reported. 46 A case of liquid evacuation has also been reported in a patient with HIV/AIDS.…”
Section: Vibrio Fluvialismentioning
confidence: 99%
“…cholerae em seu modo de ação, tipo de receptor e antigenicidade (AHSAN et al, 1988), o que está de acordo com o fato de V. fluvialis não possuir o gene responsável pela codificação da toxina colérica (NISHIBUCHI e SEIDLER, 1983;.…”
Section: Fatores De Virulência E Resistência a Antibióticosunclassified